Family Medicine Training in Lesotho: A Strategy of Decentralized Training for Rural Physician Workforce Development - Bryden, Benjamin; Bryden, Mariel; Steer-Massaro, Jonathan; Malope, Sebaka (Frontiers in Medicine, 2021)
Family medicine is a relatively new but rapidly expanding medical discipline in sub Saharan Africa. Specialization in Family Medicine is an effective means for building and retaining a highly skilled rural physician workforce in low- and middle-income countries. The Lesotho Boston Health Alliance Family Medicine Specialty Training Program is the first and only post-graduate family medicine program and the only accredited post-graduate training program in the Kingdom of Lesotho. Lesotho has unique challenges as a small mountainous enclave of South Africa with one of the lowest physician-to-patient ratios in the world. Most health professionals are based in the capital city, and the kingdom faces challenging health problems such as high HIV prevalence, high maternal mortality, and malnutrition, as well as increasing burdens of non-communicable diseases such as hypertension, diabetes, and obesity. In response to these health crises and the severe shortage of health professionals, Lesotho Boston Health Alliance partnered with the Lesotho Ministry of Health in 2008 to introduce family medicine as a new specialty in order to recruit home and retain Basotho doctors. Family Medicine training in Lesotho uses a unique decentralized, non-university-based model with trainees posted at rural district hospitals throughout the country. While family medicine in Lesotho is still in the early stages of development, this model of decentralized training demonstrates an effective strategy to develop the rural health workforce in Lesotho, has the potential to change the physician workforce and healthcare system of Lesotho, and can be a model for physician training in similar environments.